2017
DOI: 10.4172/2155-9597.1000305
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Multidrug Resistant Metallo-β-Lactamases (MBLs) Positive Klebsiella Species from Cloacal Swabs of Poultry Birds

Abstract: The increasing prevalence of antibiotic resistant bacteria in the community is a public health issue because this phenomenon compromises our ability to effectively treat infectious diseases since these organisms such as those that express metallo-β-lactamase (MBL) are usually resistant to a wide variety of antibiotics. This study investigated the frequency of Klebsiella species from a local poultry farm that produced metallo-β-lactamase using phenotypic detection technique. Forty (40) samples from the cloacae … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Also in a recent study conducted in Japan, Okazaki et al [18] reported the occurrence of K. pneumoniae positive for MBL production in a non-hospital environment. We have previously reported the occurrence of MBL-producing Klebsiella species from poultry birds -in which 5 (41.7%) isolates out of 24 isolates of Klebsiella species produced MBL phenotypically [19]. This shows the impact of antibiotic misuse in the community.…”
Section: Discussionmentioning
confidence: 85%
“…Also in a recent study conducted in Japan, Okazaki et al [18] reported the occurrence of K. pneumoniae positive for MBL production in a non-hospital environment. We have previously reported the occurrence of MBL-producing Klebsiella species from poultry birds -in which 5 (41.7%) isolates out of 24 isolates of Klebsiella species produced MBL phenotypically [19]. This shows the impact of antibiotic misuse in the community.…”
Section: Discussionmentioning
confidence: 85%
“…Thongkao and Sudjaroen () also identified K. pneumoniae as a major human pathogen present in fishes obtained from retail markets. Chika, Ifeanyichukwu, Benigna, Loveday, and Stanley () in a study involving poultry cloacal swabs reported a higher prevalence rate of 60%.…”
Section: Resultsmentioning
confidence: 96%
“…While searching for newer antibiotics is one approach to tackle the problem the other option is to screen and identify potential multidrug resistant strains of pathogenic microbes so that medical researchers can use the information to estimate the relative susceptibility of resistivity of those strains and subsequently develop specific modified drug formulations that can be used to prevent the spread of such microbes. The article by Chika et al [4] presented the results of such a screening that was aimed towards the identification of multi-drug-resistant Klebsiella species isolated from cloacal swabs of poultry birds. The process of identification of MDR species was based on the presence or absence of the metallo-β-lactamase (MBL) that serves to resist the function of most antibiotics.…”
Section: Editor Notementioning
confidence: 99%